Gender-transformative Approach to Societal Empowerment. Issue 1 (June 2019) - Chintakindi, Malvya
Rural women are often termed as 'agents of change' for a successful development intervention. Women collectives as a tool/medium of change has in recent years, gained recognition as an effective intervention to empower women in developing countries. Sehgal Foundation (SF), an NGO based in Haryana, India, spearheads women collectives since 2014 to impart confidence among women representatives and strengthen their bargaining power in all walks of life. This gender-focused intervention leads to externalities that may be uncalled for and is inadequately acknowledged in the literature. An assessment of SF's work in Nuh, Haryana points to need to include men in the programme to facilitate a long-lasting and meaningful change in gender dynamics. This prerequisite to warrant social change is often implied in various research areas, that is, the importance of focusing on the community, specifically, males, for sustainable development. This essay provides empirical evidence to the same and proposes a gender-transformative approach to interventions as a solution to address gender specificity in development interventions.